A monoclonal antibody to the insect prothoracicotropic hormone - O'Brien, MA (J Neurosci, 1988)
The prothoracicotropic hormone (PTTH) is an insect cerebral peptide that stimulates the prothoracic glands to produce the steroid hormone ecdysone thus initiating molting and metamorphosis. “Big” PTTH, one of several molecular forms of the neurohormone, was isolated from brains of the tobacco hornworm Manduca sexta, and fractionated by high- pressure liquid chromatography (HPLC) for use in antibody production. A murine polyclonal antiserum and a monoclonal antibody (MAb) have been generated using this highly purified preparation of big PTTH. Antisera and hybridoma supernatants were screened with an indirect, brain whole- mount immunocytological assay, and antibody specificity was confirmed by immunocytological, ELISA, and functional criteria. In brain whole- mount preparations, the MAb (A2H5) and antiserum specifically immunostained the lateral protocerebral neurosecretory cells (L-NSC III), the prothoracicotropes, which produce PTTH. This immunostaining was blocked by preadsorbing the antibodies with big PTTH. Analysis of the elution of HPLC-fractionated big PTTH with an in vitro bioassay for the neurohormone and an ELISA employing the A2H5 MAb resulted in peaks of activity that were superimposable. Finally, the antiserum and A2H5 MAb inhibited big PTTH activation of the prothoracic glands to synthesize ecdysone in the in vitro bioassay for the neurohormone. With these specific antibodies, the organization of the PTTH neuroendocrine axis has been defined. It is now evident that both of the peptidergic neurons that comprise the L-NSC III are prothoracicotropes, and that the corpora allata are the neurohemal organs for the release of big PTTH into the hemolymph. This study indicates that these specific antibodies will be useful in investigations of numerous aspects of the biology of this cerebral neuroendocrine axis.